CHANGING INCOME STRUCTURE AND PERFORMANCE: AN EMPIRICAL ANALYSIS OF INDONESIA BANKING SECTOR 1999-2007 - Ahmad, Aula (Jurnal Analisis Bisnis Ekonomi, 2008)
This paper investigates the relationship between the changing patterns of bank's source of income and risk adjusted performance. A database of 81 banks over the period of 1999 to 2007 is concured for he 5 public sector banks and 76 private banks to compare their change in income composition. Bank's performance is measured by risk adjusted reurn on BIS risk aloocaed capital (RARORAC). We argue that in a compeitive financial market in order to change the profitability drivers in banking, Indian banks need to improve their non-interest income and also augment risk adjusted interest income through better risk based pricing.